Fertility-Sparing Surgery in Early Epithelial Ovarian Cancer: A Viable Option? - Christina Fotopoulou; Ioana Braicu; Jalid Sehouli (Obstetrics and Gynecology International)
Epithelial ovarian cancer (EOC) continues to represent one of the most lethal conditions in women in the western countries. With the shifting of childbearing towards higher age, EOC increasingly affects women with active childbearing wish, resulting in major impacts on treatment management. Next to the optimal therapeutic treatment strategies, gynecologic oncologists are being asked to incorporate into their decision-making processes the patients' wish for fertility preserving alternatives ideally without compromising oncologic safety. Nowadays, fertility-sparing surgery represents an effective alternative to conventional radical cytoreduction in younger women with early stages of the disease. As such, this paper considers indications for fertility sparing surgery in EOC, reflects on outcomes from the oncologic and reproductive data of the largest and most relevant series outcomes data, reporting on fertility sparing techniques in EOC, reviews medicamentous efforts to prevent chemotherapy induced gonadotoxicity, and discusses future aspects in the gynecologic cancer management.